A positive electrode slurry for lithium slurry battery and preparation method thereof

By adjusting the component ratio and order of the positive electrode slurry, a stable carbon glue phase is formed, and the dynamic changes in the conductive network of lithium slurry cells are solved by adjusting the component ratio and order of the positive electrode slurry, and the electrochemical performance of the slurry is improved.

CN115863541BActive Publication Date: 2025-04-18ZHENGZHOU ZHONGKE EMERGING IND TECH RES INST +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211495043.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-26
Publication Date
2025-04-18
Estimated Expiration
2042-11-26

AI Technical Summary

Technical Problem

The slurry of lithium slurry cells causes dynamic changes in the conductive network due to settlement, volume changes, etc. The active material breaks away from the conductive network, and the conductivity drops sharply, affecting the battery performance.

Method used

A positive electrode slurry including positive electrode active materials, polymer additives, conductive agents, electrolytes, crosslinking agents and initiators is used to form a stable carbon glue phase by adjusting the proportion and order of each component, and through alternate chemical crosslinking and rapid phase separation and curing, the conductive network stability and anti-settlement performance of the slurry are ensured.

Benefits of technology

The stable conductive network of the slurry and excellent settlement resistance are achieved, and the conductivity reduction and performance attenuation caused by settlement and volume changes are avoided, thereby improving the electrochemical performance of lithium slurry cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115863541B_ABST
    Figure CN115863541B_ABST
Patent Text Reader

Abstract

The present invention discloses a positive electrode slurry for lithium slurry battery and a preparation method thereof, wherein an electrolyte, a part of a conductive agent and a cross-linking agent are mixed to obtain a premixed liquid; an active material, a remaining conductive agent and a polymer additive are blended to obtain a blended dry powder, and then the premixed liquid and the blended dry powder are mixed to obtain a prefabricated slurry, and then an initiator is added to the prefabricated slurry for mixing, and the slurry is heated and frozen after mixing to obtain a positive electrode slurry. Compared with the prior art, the present invention adds a polymer additive, a cross-linking agent and an initiator, and adjusts the order and amount of use of the conductive agent, and uses a cold and hot alternating method for chemical cross-linking and rapid phase separation and curing, so that the prepared slurry has a more stable conductive network and excellent anti-sedimentation property. The battery assembled with the positive electrode slurry prepared by the present method has excellent electrochemical performance, and the preparation method is simple and easy, does not require the modification of existing production equipment, and is suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion battery manufacturing, and specifically relates to a positive electrode slurry for a lithium slurry battery and a preparation method thereof. Background Art

[0002] The depletion of fossil fuels and the deterioration of the ecological environment have prompted the world to realize the need to establish a sustainable development society. Building a clean, low-carbon, safe and efficient energy system is an effective way to build a sustainable development society and a major decision-making deployment. Energy storage is a key technology for developing large-scale applications of renewable energy and an important technical guarantee for achieving the dual carbon goals.

[0003] Compared with traditional lithium-ion batteries, all or part of the electrodes of lithium slurry batteries are composed of a slurry consisting of active material particles, conductive agents and electrolytes, which have more advantages in technical application. Lithium slurry electrodes exist in the form of slurry, which avoids the cycle life degradation problem caused by the falling off or loosening of adhesive electrode materials. The battery cycle life is longer, which is conducive to the recycling of battery materials. In addition, lithium slurry batteries can adopt ultra-thick electrode structures to effectively improve the battery energy density. The preparation of slurry electrodes eliminates the expensive preparation steps of traditional lithium-ion battery thin electrodes, such as precision coating and electrode baking, so the production process can be simplified, and it is expected that the scale production cost can be reduced to about 1 / 2 of the current lithium-ion battery.

[0004] Although lithium slurry batteries have many advantages, there are still no engineering application examples. This is mainly because in the actual application process, the internal conductive network of the slurry is in dynamic change due to sedimentation, volume change and other reasons, causing the active material to separate from the conductive network and the conductivity to drop sharply, seriously affecting the battery performance. Summary of the invention

[0005] In view of the above problems existing in lithium slurry batteries, the present invention provides a positive electrode slurry for lithium slurry batteries and a preparation method thereof. The slurry prepared by the method has a stable conductive network and anti-sedimentation performance, and the prepared lithium slurry battery has good electrochemical properties.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0007] A positive electrode slurry for a lithium slurry battery comprises a positive electrode active material, a polymer additive, a conductive agent, an electrolyte, a crosslinking agent and an initiator, wherein the mass ratio of the positive electrode active material, the polymer additive, the conductive agent and the electrolyte is (10% to 80%): (1% to 5%): (0.5% to 3%): (12% to 88%), and preferably the mass ratio of the three is (30% to 60%): (2% to 4%): (1% to 2%): (32% to 67%); the crosslinking agent accounts for 5% to 15% of the mass of the electrolyte, preferably 8% to 13%; the initiator accounts for 0.5% to 5% of the mass of the crosslinking agent, preferably 1% to 3%.

[0008] Furthermore, the positive electrode active material is one or more of lithium cobalt oxide, lithium nickel oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium manganese oxide, lithium iron phosphate, and lithium manganese iron phosphate;

[0009] Furthermore, the polymer additive is one or more of polyacrylonitrile, polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene, polyethylene oxide, polyurethane, etc.; the conductive agent is one or a mixture of conductive carbon black, conductive graphite, carbon nanotubes, graphene, carbon fiber, and Ketjen black.

[0010] Furthermore, the electrolyte includes a non-aqueous organic solvent, a lithium salt and an additive; the non-aqueous organic solvent is two or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl formate, ethyl formate, ethyl propionate, propyl propionate and methyl butyrate; the lithium salt is one or more of lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl)imide, lithium tetrafluoroborate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide and lithium perchlorate, and the lithium salt concentration is 0.6-1.2 mol / L.

[0011] Further, the cross-linking agent is one or more of polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, poly(ethylene glycol) methyl ether acrylate, and pentaerythritol triacrylate;

[0012] Furthermore, the initiator is one or more of azobisisobutyronitrile, azobisisoheptanenitrile, dibenzoyl peroxide, lauroyl peroxide, and tert-amyl peroxide pivalate.

[0013] The method for preparing the positive electrode slurry for lithium slurry battery of the present invention comprises the following steps:

[0014] (1) Mixing an electrolyte, a portion of a conductive agent and a cross-linking agent to obtain a premixed solution;

[0015] (2) blending the positive electrode active material, the remaining conductive agent and the polymer additive in proportion to obtain a blended dry powder;

[0016] (3) Mixing the premixed liquid and the blended dry powder at a certain temperature to obtain a prefabricated slurry;

[0017] (4) Adding an initiator to the prefabricated slurry and mixing them, heating the slurry after mixing, and then rapidly freezing the heated slurry to obtain a positive electrode slurry.

[0018] Furthermore, the amount of the conductive agent in step (1) accounts for 20% to 50% of the total mass of the conductive agent; the mixing method in step (1) is carried out using a double planetary stirring kettle, with a stirring speed of 10 to 60 rpm, a rotation speed of 1000 to 6000 rpm, a temperature in the stirring kettle of 25 to 45° C., and a mixing time of 0.3 to 1 h.

[0019] Furthermore, in step (2), the blending is carried out in a double planetary stirring kettle, with a stirring speed of 25 to 65 rpm, a rotation speed of 100 to 1000 rpm, a temperature in the stirring kettle of 25 to 55° C., and a stirring time of 0.5 to 2 h;

[0020] Furthermore, the mixing in step (3) is carried out in a double planetary stirring kettle, with a revolution of 40 to 80 rpm, a rotation of 1000 to 4000 rpm, a temperature in the stirring kettle of 35 to 60° C., and a stirring time of 0.5 to 2 h.

[0021] Furthermore, the mixing in step (4) is carried out by a double planetary stirring kettle, with a stirring revolution of 10 to 40 rpm, a rotation of 100 to 2000 rpm, and a temperature in the stirring kettle of 10 to 45°C; the heating temperature in step (4) is 80 to 150°C, and the heating time is 0.5 to 3 hours; the freezing temperature in step (4) is -20 to -40°C, and the freezing time is 0.5 to 3 hours; the number of heating-freezing times in step (4) is 1 to 3 times.

[0022] Compared with the prior art, the present invention has the following beneficial effects: the present invention forms a stable carbon colloid phase by adding polymer additives, crosslinking agents, initiators and adjusting the order and amount of conductive agents used, adjusting the ratio of conductive agents to polymer additives, adding conductive agents in steps to ensure stable long-range and short-range contacts between the solution and the particle surface, and using alternating hot and cold chemical crosslinking and rapid phase separation solidification, so that the prepared slurry has a more stable conductive network and better anti-sedimentation properties. During use, the present invention can prevent the separation of conductive materials from the conductive network, a sharp drop in conductivity, an increase in slurry viscosity, and performance attenuation caused by slurry sedimentation, volume change, and electrolyte volatilization. The method is simple and easy to implement, does not require additional production equipment, and is easy to industrialize. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Comparative photos of positive electrode slurry sedimentation (from left to right are Examples 1, 2, 3, and Comparative Examples 1, 2, 3). DETAILED DESCRIPTION

[0024] In order to further understand the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments to help those skilled in the art have a more complete and in-depth understanding of the concept, technical solution, etc. of the present invention and to help implement it. Obviously, the protection scope of the present invention is not limited to the following embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.

[0025] Example 1

[0026] The preparation method of the positive electrode slurry for lithium slurry battery in this embodiment is as follows:

[0027] (1) Material preparation: The mass ratio of positive electrode active material, polymer additive, conductive agent, and electrolyte is 45%:3%:2%:50%, the mass ratio of crosslinking agent to electrolyte is 13%, and the mass ratio of initiator to crosslinking agent is 2.5%. The positive electrode active material is lithium nickel cobalt manganese oxide NCM622 material, the conductive agent is conductive carbon black C65, the crosslinking agent is pentaerythritol triacrylate PETA, the initiator is azobisisobutyronitrile AIBN, the polymer additive is polyvinylidene fluoride PVDF, and the electrolyte is LiPF6 ethylene carbonate / propylene carbonate (EC / PC) solution, 1 mol / L.

[0028] (2) Premix: The electrolyte, 30% C65 and PETA were dispersed in a double planetary stirring kettle with a revolution of 40 rpm, a rotation of 3000 rpm, a temperature of 35 °C in the stirring kettle, and a stirring time of 0.5 h.

[0029] (3) Blending dry powder: Add NCM622, 70% C65 and PVDF into a double planetary stirring kettle for dispersion. Stir at an orbital speed of 40 rpm, an autorotation speed of 700 rpm, a temperature of 35 °C in the stirring kettle and a stirring time of 1 h.

[0030] (4) Pre-made slurry: Add the blended dry powder into the pre-mixed liquid for double planetary stirring and dispersion, with the stirring speed at 40 rpm, 2500 rpm, the temperature in the stirring tank at 45 °C, and the stirring time for 1 h;

[0031] (5) Positive electrode slurry: AIBN was added to the above-mentioned pre-made slurry for mixing and dispersion. The stirring speed was 25 rpm, the rotation speed was 1500 rpm, the temperature in the stirring kettle was 30°C, and the stirring time was 0.5 h. After mixing, the mixture was placed in an 85°C oven and heated for 0.5 h. Then, the mixture was placed in a -25°C freezer and frozen for 0.5 h. This heating and freezing process was repeated twice to obtain the positive electrode slurry.

[0032] Example 2

[0033] The preparation method of the positive electrode slurry for lithium slurry battery in this embodiment is as follows:

[0034] (1) Material preparation: The mass ratio of positive electrode active material, polymer additive, conductive agent, and electrolyte is 50%:3%:2%:35%, the mass ratio of crosslinking agent to electrolyte is 10%, and the mass ratio of initiator to crosslinking agent is 1.5%. The positive electrode active material is lithium nickel cobalt manganese oxide NCM622 material, the conductive agent is conductive carbon black C65, the crosslinking agent is pentaerythritol triacrylate PETA, the initiator is azobisisobutyronitrile AIBN, the polymer additive is polyvinylidene fluoride PVDF, and the electrolyte is LiPF6 ethylene carbonate / propylene carbonate (EC / PC) solution, 1 mol / L.

[0035] (2) Premix: The electrolyte, 50% C65 and PETA were dispersed in a double planetary stirring kettle with a revolution of 40 rpm, a rotation of 3000 rpm, a temperature of 35 °C in the stirring kettle, and a stirring time of 0.5 h.

[0036] (3) Blending dry powder: Add NCM622, 50% C65 and PVDF into a double planetary stirring kettle for dispersion. Stir at 40 rpm, 700 rpm, 35 °C in the stirring kettle, and 1 h.

[0037] (4) Pre-made slurry: Add the blended dry powder into the pre-mixed liquid for double planetary stirring and dispersion, with the stirring speed at 40 rpm, 2500 rpm, the temperature in the stirring tank at 45 °C, and the stirring time for 1 h;

[0038] (5) Positive electrode slurry: AIBN was added to the above-mentioned pre-made slurry for mixing and dispersion. The stirring speed was 25 rpm, the rotation speed was 2000 rpm, the temperature in the stirring kettle was 30 °C, and the stirring time was 0.5 h. After mixing, the mixture was placed in an 85 °C oven and heated for 0.5 h. Then, the mixture was placed in a -35 °C freezer and frozen for 1 h. This heating-freezing process was repeated three times to obtain the positive electrode slurry.

[0039] Example 3

[0040] The preparation method of the positive electrode slurry for lithium slurry battery in this embodiment is as follows:

[0041] (1) Material preparation: The mass ratio of positive electrode active material, polymer additive, conductive agent, and electrolyte is 60%:3%:2%:35%, the mass ratio of crosslinking agent to electrolyte is 8%, and the mass ratio of initiator to crosslinking agent is 2.5%. The positive electrode active material is lithium nickel cobalt manganese oxide NCM622 material, the conductive agent is conductive carbon black C65, the crosslinking agent is pentaerythritol triacrylate PETA, the initiator is azobisisobutyronitrile AIBN, the polymer additive is polyvinylidene fluoride PVDF, and the electrolyte is LiPF6 ethylene carbonate / propylene carbonate (EC / PC) solution, 1 mol / L.

[0042] (2) Premix: The electrolyte, 20% C65 and PETA were dispersed in a double planetary stirring tank with a revolution of 40 rpm, a rotation of 3000 rpm, a temperature of 35 °C in the stirring tank, and a stirring time of 0.5 h.

[0043] (3) Blending dry powder: Add NCM622, 80% C65 and PVDF into a double planetary stirring kettle for dispersion. Stir at a revolution of 40 rpm, a rotation of 1000 rpm, a temperature of 35 °C in the stirring kettle, and a stirring time of 1.5 h.

[0044] (4) Pre-made slurry: Add the blended dry powder into the pre-mixed liquid for double planetary stirring and dispersion, with the stirring speed at 40 rpm, 2500 rpm, the temperature in the stirring tank at 45 °C, and the stirring time for 1 h;

[0045] (5) Positive electrode slurry: Add AIBN to the above-mentioned prefabricated slurry and mix and disperse it. Stir at an orbital speed of 25 rpm and an autorotation speed of 2000 rpm. The temperature in the stirring kettle is 30°C and the stirring time is 0.5 h. After mixing, put it into an 85°C oven and heat it for 0.5 h. Then put it into a -35°C freezer and freeze it for 1 h to obtain the positive electrode slurry.

[0046] Comparative Example 1

[0047] The difference between this comparative example and Example 1 is that AIBN is not added in step (5). The specific steps are as follows:

[0048] (1) Material preparation: The mass ratio of positive electrode active material, polymer additive, conductive agent, and electrolyte is 45%:3%:2%:50%. The positive electrode active material is lithium nickel cobalt manganese oxide NCM622 material, the conductive agent is conductive carbon black C65, the crosslinking agent is pentaerythritol triacrylate PETA, the initiator is azobisisobutyronitrile AIBN, the polymer additive is polyvinylidene fluoride PVDF, and the electrolyte is LiPF6 ethylene carbonate / propylene carbonate (EC / PC) solution, 1 mol / L.

[0049] (2) Premixed liquid: The electrolyte and 30% C65 were dispersed in a double planetary stirring kettle with a revolution of 40 rpm and a rotation of 3000 rpm. The temperature in the stirring kettle was 35 °C and the stirring time was 0.5 h.

[0050] (3) Blending dry powder: Add NCM622, 70% C65 and PVDF into a double planetary stirring kettle for dispersion. Stir at an orbital speed of 40 rpm, an autorotation speed of 700 rpm, a temperature of 35 °C in the stirring kettle and a stirring time of 1 h.

[0051] (4) Pre-made slurry: Add the blended dry powder into the pre-mixed liquid for double planetary stirring and dispersion, with the stirring speed at 40 rpm, 2500 rpm, the temperature in the stirring tank at 45 °C, and the stirring time for 1 h;

[0052] (5) Positive electrode slurry: Mix and disperse the above prefabricated slurry, stir at 25 rpm, 1500 rpm, 30°C in the stirring kettle, and stir for 0.5 h. After mixing, place in an 85°C oven and heat for 0.5 h. Then place in a -25°C freezer and freeze for 0.5 h. Repeat this process twice to obtain the positive electrode slurry.

[0053] Comparative Example 2

[0054] The difference between this comparative example and Example 2 is that the drying-freezing operation is not performed in step (5). The specific steps are as follows:

[0055] (1) Material preparation: The mass ratio of positive electrode active material, polymer additive, conductive agent, and electrolyte is 50%:3%:2%:35%, the mass ratio of crosslinking agent to electrolyte is 10%, and the mass ratio of initiator to crosslinking agent is 1.5%. The positive electrode active material is lithium nickel cobalt manganese oxide NCM622 material, the conductive agent is conductive carbon black C65, the crosslinking agent is pentaerythritol triacrylate PETA, the initiator is azobisisobutyronitrile AIBN, the polymer additive is polyvinylidene fluoride PVDF, and the electrolyte is LiPF6 ethylene carbonate / propylene carbonate (EC / PC) solution, 1 mol / L.

[0056] (2) Premix: The electrolyte, 50% C65 and PETA were dispersed in a double planetary stirring kettle with a revolution of 40 rpm, a rotation of 3000 rpm, a temperature of 35 °C in the stirring kettle, and a stirring time of 0.5 h.

[0057] (3) Blending dry powder: Add NCM622, 50% C65 and PVDF into a double planetary stirring kettle for dispersion. Stir at 40 rpm, 700 rpm, 35 °C in the stirring kettle, and 1 h.

[0058] (4) Pre-made slurry: Add the blended dry powder into the pre-mixed liquid for double planetary stirring and dispersion, with the stirring speed at 40 rpm, 2500 rpm, the temperature in the stirring tank at 45 °C, and the stirring time for 1 h;

[0059] (5) Positive electrode slurry: AIBN was added to the above-mentioned prefabricated slurry for mixing and dispersion, and the stirring speed was 25 rpm, the rotation speed was 2000 rpm, the temperature in the stirring kettle was 30°C, and the stirring time was 0.5 h to obtain the positive electrode slurry.

[0060] Comparative Example 3

[0061] The difference between this comparative example and Example 3 is that the conductive carbon black C65 is added all at once in step (2). The specific steps are as follows:

[0062] (1) Material preparation: The mass ratio of positive electrode active material, polymer additive, conductive agent, and electrolyte is 60%:3%:2%:35%, the mass ratio of crosslinking agent to electrolyte is 8%, and the mass ratio of initiator to crosslinking agent is 2.5%. The positive electrode active material is lithium nickel cobalt manganese oxide NCM622 material, the conductive agent is conductive carbon black C65, the crosslinking agent is pentaerythritol triacrylate PETA, the initiator is azobisisobutyronitrile AIBN, the polymer additive is polyvinylidene fluoride PVDF, and the electrolyte is LiPF6 ethylene carbonate / propylene carbonate (EC / PC) solution, 1 mol / L.

[0063] (2) Premix: The electrolyte, 100% C65 and PETA were dispersed in a double planetary stirring kettle with a revolution of 40 rpm, a rotation of 3000 rpm, a temperature of 35 °C in the stirring kettle, and a stirring time of 0.5 h.

[0064] (3) Blending dry powder: Add NCM622 and PVDF into a double planetary stirring kettle for dispersion, with a stirring speed of 40 rpm, a rotation speed of 1000 rpm, a temperature of 35 °C in the stirring kettle, and a stirring time of 1.5 h;

[0065] (4) Pre-made slurry: Add the blended dry powder into the pre-mixed liquid for double planetary stirring and dispersion, with the stirring speed at 40 rpm, 2500 rpm, the temperature in the stirring tank at 45 °C, and the stirring time for 1 h;

[0066] (5) Positive electrode slurry: Add AIBN to the above-mentioned pre-made slurry and mix and disperse it. Stir at an orbital speed of 25 rpm and an autorotation speed of 2000 rpm. The temperature in the stirring kettle is 30°C and the stirring time is 0.5 h. After mixing, place it in an 85°C oven and heat it for 0.5 h. Then place it in a -35°C freezer and freeze it for 1 h. Repeat this process once to obtain the positive electrode slurry.

[0067] The samples prepared in the embodiments and comparative examples were subjected to static and performance tests, and the test methods were as follows:

[0068] Conductivity test: Conduct conductivity test on the prepared slurry at 25±2℃;

[0069] Rate performance test: The slurry prepared in the slurry example and the comparative example is used to assemble a Swagelok structure battery, the slurry thickness is about 1 mm, metallic lithium is used as the counter electrode, and the 0.1C test capacity is used as a benchmark to test the capacity retention rates at 0.5C, 1.0C, and 2.0C rates, respectively.

[0070] Table 1 is the ratio and conductivity test of the embodiment and the comparative example

[0071]

[0072] By comparing the sedimentation conditions of the embodiment and the comparative example and the test results of the conductivity and rate performance, it can be seen that the polymers inside the slurry are cross-linked with each other, which improves the anti-settling performance of the slurry. Chemical cross-linking, phase separation solidification and carbon glue phase conductive network form stable ion and electron transmission channels inside the slurry, effectively improving the conductivity and rate performance of the slurry. This shows that this method can effectively improve the stability and electrochemical performance of the slurry.

[0073] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A positive electrode slurry for a lithium slurry battery, characterized in that: It includes positive electrode active material, polymer additive, conductive agent, electrolyte, crosslinking agent and initiator, wherein the mass ratio of positive electrode active material, polymer additive, conductive agent and electrolyte is (10%-80%): (1%-5%): (0.5%-3%): (12%-88%); the mass percentage of crosslinking agent in electrolyte is 5%-15%, and the mass percentage of initiator in crosslinking agent is 0.5%-5%; The method for preparing the positive electrode slurry for a lithium slurry battery comprises the following steps: (1) Mixing an electrolyte, a portion of a conductive agent and a cross-linking agent to obtain a premixed solution; (2) blending the positive electrode active material, the remaining conductive agent and the polymer additive in proportion to obtain a blended dry powder; (3) Mixing the premixed liquid and the blended dry powder at a certain temperature to obtain a prefabricated slurry; (4) adding an initiator to the prefabricated slurry and mixing them, heating the slurry after mixing, and then rapidly freezing the heated slurry to obtain a positive electrode slurry; The polymer additive is one or more of polyacrylonitrile, polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene, polyethylene oxide, and polyurethane; The amount of the conductive agent in step (1) accounts for 20% to 50% of the total mass of the conductive agent; The heating temperature in step (4) is 80 to 150° C. and the heating time is 0.5 to 3 h; The freezing temperature in step (4) is -20 to -40°C, and the freezing time is 0.5 to 3 hours; the number of heating-freezing times in step (4) is 1 to 3 times.

2. The positive electrode slurry for lithium slurry battery according to claim 1, characterized in that: The positive electrode active material is one or more of lithium cobalt oxide, lithium nickel oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium manganese oxide, lithium iron phosphate, and lithium manganese iron phosphate.

3. The positive electrode slurry for lithium slurry battery according to claim 1, characterized in that: The conductive agent is one or a mixture of conductive carbon black, conductive graphite, nano carbon tubes, graphene, and carbon fiber.

4. The positive electrode slurry for lithium slurry battery according to claim 1, characterized in that: The electrolyte comprises a non-aqueous organic solvent, a lithium salt and an additive; the non-aqueous organic solvent is two or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl formate, ethyl formate, ethyl propionate, propyl propionate and methyl butyrate; the lithium salt is one or more of lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl)imide, lithium tetrafluoroborate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide and lithium perchlorate, and the concentration of the lithium salt is 0.6-1.2 mol / L.

5. The positive electrode slurry for lithium slurry battery according to claim 1, characterized in that: The crosslinking agent is one or more of polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, poly(ethylene glycol) methyl ether acrylate, and pentaerythritol triacrylate; the initiator is one or more of azobisisobutyronitrile, azobisisoheptanenitrile, dibenzoyl peroxide, lauroyl peroxide, and tert-amyl peroxide pivalate.

6. The method for preparing a positive electrode slurry for a lithium slurry battery according to claim 1, characterized in that The following steps are involved: (1) Mixing an electrolyte, a portion of a conductive agent and a cross-linking agent to obtain a premixed solution; (2) blending the positive electrode active material, the remaining conductive agent and the polymer additive in proportion to obtain a blended dry powder; (3) Mixing the premixed liquid and the blended dry powder at a certain temperature to obtain a prefabricated slurry; (4) Adding an initiator to the prefabricated slurry and mixing them, heating the slurry after mixing, and then rapidly freezing the heated slurry to obtain a positive electrode slurry.

7. The method for preparing a positive electrode slurry for a lithium slurry battery according to claim 6, characterized in that: The mixing method in step (1) is carried out using a double planetary stirring kettle, with a stirring speed of 10 to 60 rpm, a rotation speed of 1000 to 6000 rpm, a temperature in the stirring kettle of 25 to 45° C., and a stirring time of 0.3 to 1 h.

8. The method for preparing positive electrode slurry for lithium slurry battery according to claim 6, characterized in that: In step (2), the blending is carried out in a double planetary stirring kettle, with a stirring speed of 25 to 65 rpm, a rotation speed of 100 to 1000 rpm, a temperature in the stirring kettle of 25 to 55° C., and a stirring time of 0.5 to 2 h.

9. The method for preparing positive electrode slurry for lithium slurry battery according to claim 6, characterized in that: The mixing in step (3) is carried out in a double planetary stirring kettle, with a revolution of 40 to 80 rpm, a rotation of 1000 to 4000 rpm, an internal temperature of 35 to 60° C., and a stirring time of 0.5 to 2 h.

10. The method for preparing positive electrode slurry for lithium slurry battery according to claim 6, characterized in that: The mixing in step (4) is carried out in a double planetary stirring kettle, with a stirring speed of 10 to 40 rpm, a rotation speed of 100 to 2000 rpm, and a temperature in the stirring kettle of 10 to 45°C.

Citation Information

Patent Citations

  • Preparation method and application of graphene slurry

    CN105060283A

  • Preparation method of lithium battery slurry and application thereof

    CN110061222A